Electronic government maturity stage, user’s adoption and user’s satisfaction level / Mas Anom Abdul Rashid - Abdul Rashid, Mas Anom (Institute of Graduate Studies, UiTM, 2012)
E-government is the use of information communication technology in deliver ring public service via internet (webbased). Western countries are convinced that the information society will result in economic and social benefits. The Organisation for Economic Cooperation and Development believes that information infrastructures are expected to stimulate economic growth, increase productivity, create jobs and improve the quality of life, and that is why Malaysia in its New Economic Model 2010 (NEM, 2010) has put government public service as the second pillar to upgrade the quality of the citizens’ lives. To achieve e-government success, the government has to evaluate each e-government project at every government administration level, namely the federal, state, local and municipal.